Evaluasi Kesesuaian Lahan Tanaman Padi Sawah (Oryza sativa L.) Di Desa Sukorejo Kecamatan Sei Balai Kabupaten Batubara - deyu zahraini putri; purba marpaung; mariani br sembiring (Jurnal Agroekoteknologi, 2018)
Land evaluation is estimation process of the potensial land for a variety of alternative uses optimally by considering physical and socioeconomic factors as well as conservation of environmental resources for sustainable use. This study aimed to evaluate the suitability of  rice paddy (Oryza sativa L.) in Village Sukorejo Subdistric Sei Balai Distric Batubara. It can be obtained 2 (two) Land Mapping Unit (SPL) which is determined base on the overlay result from the map of topography, map of soil types and map of land use with scale of 1 : 20.000 that is Sawah Ultisol SPL 1A and 1B and Sawah Inceptisol SPL 2A and 2B. This study used survey method and the class assessment of land suitability was done by matching based on criteria astablished by Peraturan Mentri Pertanian No.79 (2013). The results showed that the land suitability classes of actual rice paddy (Oryza sativa L.) in SPL 1A, 1B and 2A is Marginally Suitable/ S3nrxs by a nutrient retention and sulfidic material barrier factor while in SPL 2B is Marginally Suitable/S3nr by a nutrient retention barrier factor. The land suitability calasses potential rice paddy (Oryza sativa L.) for l SPL (1A, 1B dan 2A) is suitable/ S2nrxs by a nutrient retention and sulfidic material barrier factor while in SPL 2B is suitable/ S2nr by a nutrient retention barrier factor. Keywords : Land suitability, Lowland rice, Rice paddy